2009
DOI: 10.3201/eid1503.081007
|View full text |Cite
|
Sign up to set email alerts
|

Coccidioidal Pneumonia, Phoenix, Arizona, USA, 2000–2004

Abstract: Community-acquired pneumonia (CAP) often results in severe illness and death. In large, geographically defi ned areas where Coccidioides spp. are endemic, coccidioidomycosis is a recognized cause of CAP, but its frequency has not been studied extensively. To determine the frequency of patients with coccidioidomycosis, we conducted a prospective evaluation of 59 patients with CAP in the Phoenix, Arizona, area. Of 35 for whom paired coccidioidal serologic testing was performed, 6 (17%) had evidence of acute cocc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…Clinical investigations have revealed that reactivation of coccidioidomycosis in people who initially have an asymptomatic coccidioidal infection can occur months to years after exposure to the pathogen during a visit to an endemic site [8•]. Major outbreaks of coccidioidomycosis continue to occur, particularly in California and Arizona [9, 10]. For example, a huge dust storm that swept through Phoenix on 5 July 2011 resulted in a significant rise in the number of symptomatic infections during the following 4-month period (http://www.vfce.arizona.edu/resources/pdf/SunenshineMD-AM_CME_Cocci_Epi_11_6_11.pdf).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical investigations have revealed that reactivation of coccidioidomycosis in people who initially have an asymptomatic coccidioidal infection can occur months to years after exposure to the pathogen during a visit to an endemic site [8•]. Major outbreaks of coccidioidomycosis continue to occur, particularly in California and Arizona [9, 10]. For example, a huge dust storm that swept through Phoenix on 5 July 2011 resulted in a significant rise in the number of symptomatic infections during the following 4-month period (http://www.vfce.arizona.edu/resources/pdf/SunenshineMD-AM_CME_Cocci_Epi_11_6_11.pdf).…”
Section: Introductionmentioning
confidence: 99%
“…Valdivia and coworkers (50) reported that 29% of patients diagnosed with CAP in Tucson, AZ, had contracted coccidioidomycosis. Physicians are strongly advised to consider Coccidioides infection in their differential diagnosis of all patients with CAP who reside in or have recently visited a region to which coccidioidal disease is endemic (26). Coccidioidal infections can progress to life-threatening, chronic progressive pneumonia, extrapulmonary nonmeningeal disease, or meningitis, the most feared complication of coccidioidomycosis (36).…”
mentioning
confidence: 99%
“…911 Once inside the host, Coccidioides produces spherules, specialized parasitic structures that reinfect host tissues and disseminate inside the host. 12 In most cases, infection is asymptomatic, and the majority of symptomatic cases present as a flu-like illness; 13,14 however, some cases can result in a chronic or disseminated life-threatening disease. 15 …”
Section: Introductionmentioning
confidence: 99%